A progress review of entrepreneurship and regional development: What are the remaining gaps?. Issue 6 (2nd June 2016) - Müller, Sabine
ABSTRACT: This study reviews the literature related to regional entrepreneurship. It identifies the main topical perspectives, advancements and shortcomings, discusses several research gaps and proposes ways forward. The literature review is based on 170 peer-reviewed articles in the leading journals of entrepreneurship and regional science. The findings reveal that major debates occur within the disciplines of regional economics, sociology and economic geography, but discussions across disciplines are scant. While regional economists tend to overlook the role of contextualized agency, and thus neglect processes that may influence entrepreneurs' acting in distinctive localities, entrepreneurship scholars tend to overlook the role of the spatial and proximate contextual conditions in the entrepreneurial process. Future research should intensify its efforts on the interrelation between entrepreneurial agency and regional structuring in order to expand current understandings of which types of entrepreneurship prevail in different localities.